The Influence of Cross-Border Cooperation on the Competitiveness of Euroregions - Friedrichs, Marco Jerome (Jihočeská univerzita, 2021)
This master's thesis analyses the influence of cross-border cooperation on the competitiveness of Euroregions by means of a comparative case study of two selected Euroregions: the Greater Region at the intersection of the borders between the states of Belgium, France, Luxembourg and Germany, and the Euregio Egrensis, covering territories of the Czech Republic and the three German Länder Bavaria, Saxony and Thuringia. The research objective raised first and foremost two questions: How to measure the influence of cross-border cooperation and how to measure the competitiveness of (Euro)regions? This thesis is therefore divided into two parts. First, the key concepts of Euroregions, cross-border cooperation and regional competitiveness are discussed at length as all of them are demanding notions in their own right and their understanding critical for the success of the subsequent comparative case study, which then forms this thesis's second part.
The Influence of Cross-Border Cooperation on the Competitiveness of Euroregions
Keywords: Euroregions; cross-border cooperation; borders; border regions; regional competitiveness; comparative case study; Greater Region; Euregio Egrensis; Euroregions; cross-border cooperation; borders; border regions; regional competitiveness; comparative case study; Greater Region; Euregio Egrensis